THE EFFECT OF PRODUCT QUALITY AND PRICE ON LOYALTY OF TELKOMSEL PREPAID CARD USERS WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE - Puspita, Dela; Sarmigi, Elex; Azhar, Azhar (Distribusi - Journal of Management and Business, 2024)
This study aims to examine the Influence of Product Quality and Price on the Loyalty of Telkomsel Prepaid Card Users with Customer Satisfaction as a Mediating Variable. This research employs a quantitative method with a sample size of 101 respondents who are Telkomsel card users in Sungai Penuh City, calculated based on the Lemeshow formula. Data was collected using a questionnaire distributed online via Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that price has a positive effect on customer satisfaction. Price does not have an effect on consumer loyalty. Customer satisfaction has a positive effect on consumer loyalty. Product quality has a positive effect on customer satisfaction. Product quality does not have an effect on consumer loyalty. The study also proves that customer satisfaction does not mediate the relationship between price and consumer loyalty, but customer satisfaction does mediate the relationship between product quality and consumer loyalty.